Disentangling the effects of climate, density dependence, and harvest on an iconic large herbivore's population dynamics. Issue 4 (1st June 2015) - Koons, David N.; Colchero, Fernando; Hersey, Kent; Gimenez, Olivier
Abstract : Understanding the relative effects of climate, harvest, and density dependence on population dynamics is critical for guiding sound population management, especially for ungulates in arid and semiarid environments experiencing climate change. To address these issues for bison in southern Utah, USA, we applied a Bayesian state‐space model to a 72‐yr time series of abundance counts. While accounting for known harvest (as well as live removal) from the population, we found that the bison population in southern Utah exhibited a strong potential to grow from low density (β0 = 0.26; Bayesian credible interval based on 95% of the highest posterior density [BCI] = 0.19–0.33), and weak but statistically significant density dependence (β1 = −0.02, BCI = −0.04 to −0.004). Early spring temperatures also had strong positive effects on population growth (βfat1 = 0.09, BCI = 0.04–0.14), much more so than precipitation and other temperature‐related variables (model weight > three times more than that for other climate variables). Although we hypothesized that harvest is the primary driving force of bison population dynamics in southern Utah, our elasticity analysis indicated that changes in early spring temperature could have a greater relative effect on equilibrium abundance than either harvest or the strength of density dependence. Our findings highlight the utility of incorporating elasticity analyses into state‐space population models, and the need to include climatic processes in wildlife management policies and planning.